Seals of the Rightly-Guided Caliphs and Their Signs - Saleh, Omar Amjad (Journal of Tikrit University for Humanities, 2020)
The current study deals with the inscriptions of the rightly-guided caliphs Abu Bakr, Omar, Uthman and Ali (May Allah be pleased with them), but in different way, since this study does not rely on saying narratives to achieve the historical purpose of the topic only. Then starting with the main goal of this study related to the inscription of these seals of the rightly-guided caliphs, and what they represent as the slogan of the authority, then carefully examining the impact of these inscriptions, and trying to analyze their semantic and psychological meanings and effected on each side of the caliphs personalities, to uncover the main reasons behind using these seals in the right place and time. In order to form the frameworks of the equation of influence and the reverse impact of these inscriptions between the inscription itself, and its bearer or its inscription, so that it becomes clear to the researcher that the issue of the intended effect is what the owner of the inscription wanted from his inscription and taking, in contrast aspects of his personality and belief, spiritual, and psychological beliefs to bring us this meaning and the verbal meaning that was depicted on the inscription itself. As for the issue of being affected by the seal is that the personality of the owner of the seal is influenced by its inscription. In fact, the inscription became a vow and reminder or an admonish to its bearer. Moreover, it was a means to stimulate him in adopting the correct and righteous approach in caring for the nation’s affairs as he is the guardian of Muslims, to establish justice among people and to reach the desired.